PEMANFAATAN BUDAYA TRADISIONAL UNTUK MEMBANTU KEGIATAN INVESTIGASI PADA PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN MATEMATIKA REALISTIK - Chairunisah Chairunisah (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2015)
Various studies present students’ difficulties in mathematization. in learning process, the using of formula tend to be provided quickly without involving the conceptual basis and children’s daily experiences in investigating problem solving. For this reason, the teaching and learning was designed linking to a set of students’ experience-based activities. This study presents the students’ activities framework in using local culture activities as a context to encourage the guided reinvention in mathematization. The study is situated in the context of implementing an Indonesian version of Realistic Mathematics Education, labeled as PMRI in Indonesia. This situation brings the students to investigative mathematization.